Detection and antimicrobial resistance profile of campylobacter spp. in retail chicken meat from selected Davao City public markets - Durano, Lourivy P. (2016.)
Campylobacter is one of the emerging foodborne pathogens alongside pathogenic Escherichia coli, Salmonella, Shigella and Trichinella (WHO, 2013). In particular, Campylobacter jejuni, a foodborne pathogen, is the most common cause of bacteria-mediated diarrheal disease worldwide and most studies have pointed out poultry and poultry products consumption as the primary risk factor in acquiring the infection (Yang, et al., 2003; Humphrey, et al., 2006; Wingstrand, et al., 2006). Aside from increasing human Campylobacter infections worldwide. The rapid emergence of antibiotic-resistant strains pose a threat in both medical and veterinary sectors (Alfredson & Korolik, 2007). Thus, this study was conducted to determine the presence and antimicrobial resistance profile of Campylobacter spp. In retail chicken meat from selected public markets in Davao City. A total of 136 out of 170 retail chicken meat tested, 80% (CI: 73.99-86.01) were found to be contaminated with Campylobacter spp. Althogether, the antimicrobial resistance profile of 134 isolates were determined. Of these , all isolates (100%) were resistant to tetrcycline, followed by erythromycine, 99.25%; ciprofloxacin, 98.51%; clindamycin, 97.76%; chloramphenicol, 70.15%; and gentamicin, 52.99%. Of the 134 isolates, 56 (41.79%) were found to be resistant to five antimicrobial agents, 53 (39.55%) were resistant to all antimicrobial agents, 22 (16.42%) were resistant to four antimicrobial agents. Consequently, all isolate were resistant to at least two antimicrobial agents tested and 97.76% (131 out of 134) were multi-drug resistant or resistant to four or more agents. These findings suggest the potential of chicken meat as a crucial vehicle of multi-drug resistant campylobacteriosis to susceptible host in Davao City and efforts to reduce the risk of acquiring this organism should be taken into consideration.
Available in CD, pdf copy.
Thesis (Master of Science in Public Health, Medical Microbiology)--University of the Philippines Manila.
Keywords: Campylobacter jejuni; Campylobacter infections in poultry